A Comparative Analysis of the Effectiveness of Design Coordination Based on Building Information Modeling (BIM) Using A Value Stream Mapping Approach in Highway Infrastructure Projects - Rezeki Fajri; Muhammad Isradi (Eduvest - Journal of Universal Studies, 2026)
Design coordination in toll road projects involves many stakeholders with high information exchange needs, potentially causing process waste such as waiting time, repeated inspections, design revisions, and information delays, which reduces coordination effectiveness and impacts design completion duration. The application of Building Information Modeling (BIM) through the Common Data Environment (CDE) is expected to enhance information integration and collaboration among stakeholders, thereby increasing design coordination effectiveness. This study aims to analyze the effectiveness of the application of BIM-CDE in the design coordination process in toll road infrastructure projects through waste identification and process performance measurement. The research uses a mixed methods approach with a case study design. Data were obtained through observation, study of project documents, and semi-structured interviews. The analysis was carried out using Value Stream Mapping (VSM) to identify Value Added (VA), Non-Value Added (NVA), and supporting activities, then evaluated using waiting time, lead time, and Process Cycle Efficiency (PCE) indicators. The results of the study identified four types of waste, namely waiting, transportation, defect, and overprocessing. The implementation of BIM-CDE was able to reduce the waiting time from 72 days to 25 days (65.28%), while the total lead time was reduced from 255 days to 134 days (47.45%). In addition, the PCE value increased from 27.45% to 31.34% indicating an improvement in process efficiency. This study was limited to one project case study so generalizations of results are still limited. Further research is suggested to test the application of BIM–CDE on different projects.